Serial Verb Nominalization In Akan: The Question Of Intervening Elements - Kambon, Ọbádélé Bakari; Duah, Reginald Akuoko; Appah, Clement Kwamina Insaidoo (My University, 2019)
In this paper, we hope to disambiguate the nature of look-alike intervening elements that appear between verbs in Serial Verb Constructions (SVCs) and Serial Verb Construction Nominalizations (SVCNs). To do so, we will first show that these intervening elements share the same phonological form. We will then show that although the intervening elements look the same on the surface, they can be differentiated by appealing to semantics and the construction from which the SVCN is derived. In doing so, we find that some of the intervening elements should, indeed, be regarded as tamp markers, while others are nominalizers (nmlz). In conclusion, we identify abstract schemata/templates that account for, and predict the positioning of, intervening elements found in Akan SVCNs.
Keywords: Akan; Serial verb nominalization; intervening elements